Integrated River Basin Governance - Hooper, Bruce (IWA Publishing, 2005)
Integrated River Basin Governance - Learning from International Experience is designed to help practitioners implement integrated approaches to river basin management (IRBM). It aims to help the coming generation of senior university students learn how to design IRBM and it provides current researchers and the broader water community with a resource on river basin management. Drawing on both past and present river basin and valley scale catchment management examples from around the world, the book develops an integration framework for river basin management. Grounded in the theory and literature of natural resources management and planning, the thrust of the book is to assist policy and planning, rather than extend knowledge of hydrology, biophysical modelling or aquatic ecology. Providing a classification of river basin organizations and their use, the book also covers fundamental issues related to implementation: decision-making. institutions and organizations. information management. participation and awareness. legal and economic issues. integration and coordination processes. building human capacity. Integrated River Basin Governance focuses on the social, economic, organizational and institutional arrangements of river basin management. Methods are outlined for implementing strategic and regional approaches to river basin management, noting the importance of context and other key elements which have been shown to impede success. The book includes a range of tools for river basin governance methods, derived from real life experiences in both developed and developing countries. The successes and failures of river basin management are discussed, and lessons learned from both are presented.